Gestão de processos em instituições de ensino:caso Universidade Veiga de Almeida - Sarquis, Antonio Carlos da Fonseca (2002)
The great current chalienges faced by the countries are intimately related with continue and deep social transformations caused by the speed with that new scientiflc and technological knowledge have been generated. Nowadays, the complex demands of the societies are assisted by knowledge of scientific base. Besides, the generation of base technologies informs that it demands investments in research and technology. For so much, it is believed that is necessary a complete revision methodological and content in the universities, given that in the last decades the coming demands of the job market developed more quickly than the capacity of adaptation of the education system to assist them. The Universidade Veiga de Almeida, emphasizing the concept of the importance of customers and services rendered, implants the beginnings of the Administration of Processes, demonstrating that these, when applied with opportunity and correction, can present improvement of lhe teaching. One of the great problems faced by the academic administration, was the lack of information requested by the students, it is long in the service of their processes and the synergy lack between yours administrative sections. Then was created the General Qifice of Service appeared to the Students, that ii starts then to assume this integration paper, falling to the Coordinators of lhe courses an action returned to lhe side academic-pedagogic, what carted an improvement in the quality of the teaching of the courses of the UVA.